KNOWLEDGE BASIS ON FOREIGN EQUIPMENT FOR EXTRACTION OF PLANT RAW MATERIALS - Shegelman I. R., Sukhanov I. V., Vasilyev A. S. (Education and science in the modern context, 2019)
knowledge bases are needed in scientific and technical search for the synthesis of new patentable technical solutions. A knowledge base is being formed on foreign equipment on the market for extractors of components of plant materials.
Keywords: база знаний; knowledge base; рынок зарубежного оборудования; экстрактор растительного сырья; foreign equipment market; plant extractor